E-infrastuctures and e-services for developing countries second international ICST conference, AFRICOM 2010, Cape Town, South Africa, November 25-26, 2010, revised selected papers - Popescu-Zeletin, Radu; Rai, Idris A.; Jonas, Karl; Villafiorita, Adolfo (Lecture notes of the institute for computer sciences, social informatics and telecommunications engineering, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International ICST Conference on e-Infrastructure and e-Services for Developing Countries, AFRICOM 2010, held in Cape Town, South Africa, in November 2010. The 13 revised full papers presented were carefully reviewed and selected and cover a wide range of topics such as wireless network technologies, E-governance, as well as ICT for development and ICT business models and open-access.